Perceived built environment characteristics associated with walking and cycling across 355 communities in 21 countries. (January 2023) - Boakye, Kwadwo; Bovbjerg, Marit; Schuna, John; Branscum, Adam; Mat-Nasir, Nafiza; Bahonar, Ahmad; Barbarash, Olga; Yusuf, Rita; Lopez-Jaramillo, Patricio; Seron, Pamela; Rosengren, Annika; Yeates, Karen; et al.
Abstract: Research examining built environment (BE) characteristics and walking/cycling behaviors has been conducted primarily in high-income countries and conclusions cannot be applied directly to low- and middle-income countries. We evaluated perceived BE characteristics and walking/cycling behaviors across 355 urban communities in 21 low-, middle-, and high- income countries using individual data for 39, 908 adults in the Prospective Urban and Rural Epidemiology study. The 1-week long-form International Physical Activity Questionnaire was used to measure walking/cycling behaviors. Perceived BE characteristics were measured using the Neighborhood Environment Walkability Scale. Mixed effects logistic regression models examined associations between BE measures and walking for transport (≥150 min/wk), walking for leisure (≥150 min/wk), and any cycling for transport, controlling for individual, household, and community factors. Land-use mix diversity, land-use mix access, and street connectivity were associated with higher odds of walking for transport. Land-use mix diversity, land-use mix access, safety from traffic and safety from crime were associated with higher odds of walking for leisure. Land-use mix diversity, land-use mix access, and aesthetics were associated with higher odds of cycling. Differences in associations were observed by country-income status. Our findings can help guide policy makers globally to implement BE design to encourage walking and cycling behaviors. Highlights: Wide variation in the prevalence of walking/cycling behaviors across country development levels. Specific built environment measures associated with increased odds of walking/cycling. Different built environment characteristics support cycling and walking differently. Many associations differed by country income status.